Neutron scattering of sandstone subjected to uniaxial compression in cryogenic conditions - Dr Nadimul Faisal; Dr Tung Lik Lee; Dr Joe Kelleher; Dr Reza Sanaee; Dr Ketan Pancholi (ISIS Facility, 2019)
The exploitation of unconventional remote geological resources, such as those in Arctic formations, requires engineering designs that withstand the temperatures and pressures encountered. In a previous experiment (RB1810235, April 2018) comparing sandstone and limestone, we showed that limestone can mainly have tensile residual strains, while sandstone has compressive residual strains under otherwise similar thermal and loading conditions. Not enough experimental time was available in the previous beamtime to fully characterise sandstone however; therefore, this continuation proposal is to study frozen (cryogenic conditions) sandstone subjected to unconfined uniaxial compression loading conditions. In this proposal we aim to test core sandstone samples at high pressure (5-15 MPa) and low temperature conditions (as low as -5°C, -30°C).